PENGARUH KOMPETENSI PROFESIONAL GURU DALAM MEMANFAATKAN LINGKUNGAN SEBAGAI SUMBER BELAJAR TERHADAP HASIL BELAJAR SISWA SMA NEGERI DI KABUPATEN PELALAWAN - Rediana Manurung; Dede Sugandi; Epon Ningrum (Jurnal Ilmu Lingkungan, 2021)
Utilization of the environment as a learning resource is expected to influence student activities so that student learning outcomes are maximized. Therefore, it is necessary to have the support of teachers who have professional competence in learning geography. The purpose of this study was to determine the effect of teacher professional competence in utilizing the environment on student learning outcomes at SMA Negeri Pelalawan. The research method used in this study is a descriptive study method, using a quantitative approach. The population in this study were teachers of geography as well as students of class X Social Sciences in SMA Negeri Pelalawan totaling 52 teachers and 552 students of class X Social Sciences. The number of samples used were 4 teachers of geography and 135 students of class X IPS. The test used is linear regression test. The results of this study are that there is a relationship between the professional competence of geography teachers in utilizing the school environment on student learning outcomes with sig. = 0.000. The value of the regression equation for teacher professional competence on learning outcomes is Y= 17.696 + 0.371X. The value of R square is 0.329. This value implies that the effect of teacher professional competence (X) on learning outcomes (Y) is 32.9%, while 67.1% is influenced by other variables not examined. Suggestions for teachers to improve professional competence, so that they can carry out their professional duties as a teacher well in order to achieve the learning objectives that have been set.